Toxicity, Efficacy, and Quality of Life of Addition of IMRT Boost to Whole Brain Radiation Therapy and Concurrent Temozolomide in Patients with Newly Diagnosed Brain Metastases - Thimmaiah, Naveen; G V, Ajay; Loni, Rahul; Pasha, Tanvir; Sridhar, Poojar; V, Lokesh (Reports of Radiotherapy and Oncology, 2015)
Background: Brain metastasis is the most common intracranial tumor in adults. Addition of boost dose to brain metastases with stereotactic radiosurgery following whole brain radiation therapy with concurrent temozolomide showed improved outcomes; hence, the current study aimed at evaluating toxicity, efficacy, and quality of life (QOL) of addition of intensity-modulated radiation therapy (IMRT) boost to whole brain radiation therapy (WBRT) and concurrent temozolomide (TMZ) in patients with newly diagnosed brain metastases. Methods: Twenty patients with known primary histology, newly diagnosed brain metastases, underwent recursive partitioning analysis (RPA) class I/II, and fulfilling eligibility criteria were enrolled in the current study. Patients who initially received WBRT with concurrent TMZ were randomly assigned to receive IMRT boost to an additional 20 Gray (group A) or no further treatment (group B). Serial evaluations of toxicity (hematologic and non-hematologic), response (clinical, neurologic, and radiologic), and QOL were performed at 3 months and 6 months after the completion of Radiotherapy. The 2 groups were compared for toxicity, response, and QOL by appropriate statistical tests. Results: At the median follow-up of 5 months, patients in group A demonstrated similar toxicity, superior response, and better QOL in 3 domains (physical functioning, role functioning, and global health status). Conclusions: Addition of IMRT boost to WBRT and TMZ provided superior response and better QOL, without additional toxicity, compared with WBRT alone.